2009
DOI: 10.1016/j.stem.2009.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog Signaling Is Dispensable for Adult Murine Hematopoietic Stem Cell Function and Hematopoiesis

Abstract: SUMMARY We report the unexpected finding that loss of Hh signaling through conditional deletion of Smoothened (Smo) in the adult hematopoietic compartment has no apparent effect on adult hematopoiesis, including peripheral blood count, number or cell-cycle status of stem or progenitor cells, hematopoietic colony-forming potential, long-term repopulating activity in competitive repopulation assays, or stress response to serial 5-fluorouracil treatment. Furthermore, pharmacologic inhibition of Hh signaling with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
136
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(139 citation statements)
references
References 36 publications
3
136
0
Order By: Relevance
“…Moreover, the Hh pathway seems to be essential in the survival and expansion of BcrAbl þ leukemic stem cells (Dierks et al, 2008). In line with these findings, Zhao and colleagues (Zhao et al, 2009) recently showed that Hh signaling has an important role in hematopoietic stem cell self-renewal and in maintenance of cancer stem cells in leukemia, although the loss of Hh signaling through conditional deletion of Smo in the adult hematopoietic compartment had no apparent effect on adult hematopoiesis in mice (Hofmann et al, 2009), warranting further studies as to its actual role in the hematopoietic compartment. Together, these considerations prompt further investigation into the potential role of the Hh pathway in the pathophysiology of leukemic disease.…”
Section: Introductionmentioning
confidence: 91%
“…Moreover, the Hh pathway seems to be essential in the survival and expansion of BcrAbl þ leukemic stem cells (Dierks et al, 2008). In line with these findings, Zhao and colleagues (Zhao et al, 2009) recently showed that Hh signaling has an important role in hematopoietic stem cell self-renewal and in maintenance of cancer stem cells in leukemia, although the loss of Hh signaling through conditional deletion of Smo in the adult hematopoietic compartment had no apparent effect on adult hematopoiesis in mice (Hofmann et al, 2009), warranting further studies as to its actual role in the hematopoietic compartment. Together, these considerations prompt further investigation into the potential role of the Hh pathway in the pathophysiology of leukemic disease.…”
Section: Introductionmentioning
confidence: 91%
“…By contrast, CRE-mediated conditional ablation of Smo in both HSCs and their niche from embryonic stages onwards was shown to result in a profound loss of long-term grafting potential of the HSCs in vivo (Zhao et al, 2009). Yet another set of independent studies based on the conditional ablation of Smo in adult hematopoietic tissues concluded that SMO-mediated HH signaling is not required to maintain normal adult HSC function (Gao et al, 2009;Hofmann et al, 2009). In summary, the long list of discrepancies with regard to the requirement for HH in HSC function might result from a differential requirement for HH signaling in the niche versus the HSCs themselves, and/or from a different role for HH at different stages of development.…”
Section: Hematopoiesismentioning
confidence: 99%
“…Another clinical trial of GDC-0449 on a medulloblastoma patient also resulted in a rapid reduction of tumor (although transiently) but the drug resistance occurred because of SMO mutation Rudin et al, 2009). Recent results from mouse models indicate that the inhibition of Hh signaling has little effects on bone barrow stem cell population, which clears the concern of toxic effects of Hh signaling inhibition on normal stem cells Hofmann et al, 2009). Based on diversity-oriented synthesis and smallmolecule microarrays, a small-molecule robotnikinin is reported to bind Shh protein and blocks Shh signaling in cell lines, human primary keratinocytes and a synthetic model of human skin (Stanton et al, 2009).…”
Section: Small-molecule Modulators Of Hedgehog Signalingmentioning
confidence: 99%